Edoxaban treatment for pulmonary arterial thromboembolism associated with azygous vein aneurysm. Issue 3 (26th February 2017) - Mochimaru, Takao; Kawada, Ichiro; Chubachi, Shotaro; Tsutsumi, Akihiro; Hasegawa, Hanako; Betsuyaku, Tomoko
Abstract : A 76‐year‐old woman, diagnosed 5 years previously with an asymptomatic mediastinal bronchogenic cyst, was referred to our department as the mass had grown slightly larger. Contrast‐enhanced computed tomography and magnetic resonance imaging scans revealed an azygous vein aneurysm with a pulmonary arterial thromboembolism. The patient was treated with heparin for 5 days, and anticoagulation therapy with edoxaban was continued for 12 months. The thrombus resolved, and the aneurysm remained unchanged. An azygous vein aneurysm is a very rare condition that causes pulmonary arterial thromboembolism. Although surgical resection is indicated for patients with azygous vein aneurysms with a risk of rupture and pulmonary embolism, we chose anticoagulation therapy because of the patient's advanced age. This case suggests that the azygous vein aneurysm is one of the differential diagnoses for a mediastinal mass and that anticoagulation therapy can be the treatment of choice for pulmonary arterial thromboembolism with an azygous vein aneurysm. Abstract : Azygous vein aneurysm is a very rare cause of a mediastinal mass and sometimes causes pulmonary arterial thromboembolism. The treatment for azygous vein aneurysm remains controversial, but surgical resection is recommended in cases complicated by rupture, embolism, or obstruction. We present a case of pulmonary arterial thromboembolism due to an azygous vein aneurysm that is successfully treated with anticoagulation therapy (edoxaban) rather than surgical intervention.